S. Garfielde, Compiled Laws of the State of California 643-44 (1853) - (:unkn) unknown (My University, 1850)
Ch. 125, div. 4, §§ 40-41: Prohibited dueling. Should the opponent be killed, violators and their seconds shall be punished in state prison for a term not less than one year but no more than five years.
Keywords: DUELING